PEMIKIRAN PENDIDIKAN ISLAM FAZLUR RAHMAN DAN RELEVANSINYA DENGAN KURIKULUM MERDEKA BELAJAR - Ritonga, Nur’ainun; Siregar, Maragustam (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2024)
This study aims to comprehend Fazlur Rahman's educational philosophy and its relevance to the Merdeka Belajar Curriculum. Employing a literature review approach and qualitative descriptive method, the primary source is Ahmad Suryadi's book (2020) on Fazlur Rahman's educational philosophy, while secondary sources comprise relevant books and scholarly articles. Data collection techniques involve documentation, and data analysis employs the Milles and Huberman analysis technique, encompassing activities such as data reduction, data display, and conclusion drawing/verification. The research findings highlight three main concepts in Rahman's educational model: critical education, creativity, and morality, which bolster Islamic intellectualism and are pertinent to contemporary contexts. These concepts are congruent with the Merdeka Belajar concept, emphasizing student-centered learning, creativity, and the application of moral values, in accordance with Islamic principles. The relevance of Rahman's ideas to education in Indonesia demonstrates the compatibility of these concepts with the needs and context of education in the country, bolstered by various research studies.